'I can follow': self-directed informal learning strategies adopted by choristers in an adult amateur choir. (7th August 2020) - Mok, Annie O.
ABSTRACT: The qualitative study revealed how 15 choristers from an adult amateur choir with different musical experience supplemented their weekly formal choir rehearsals with self-directed informal learning strategies to learn the choral concert repertoires in Hong Kong. Semi-structured individual interviews were used to obtain data for the study. The data were processed and analysed using an adaptation of grounded theory in three steps: inductive coding and categorising; constant comparisons, and integration. The results of the analysis showed that each informant used between 3 and 6 strategies, including the aural strategies of following others and purposive listening, marking the score with sol-fa names or sight-reading, using a keyboard, technology, and some practice strategies, such as listening to a recording repeatedly in order to memorise a song. The self-directed informal mode of learning made it possible for the choristers to take ownership of and the initiative in their learning, and to learn at a pace that suited their individual needs and personal style.